Some Dioxo-metal (V & VI) Complexes of Anti-tubercular Isonicotinic Acid Hydrazide. - PANDEY, R.N.; SARITA SINGH, MRS.; KUMAR SINHA., ANIL (Asian Journal of Chemistry, 2010)
Metal complexes of anti-tubercular isonicotinic acid hydrazide drug with VO2+, MoO22+ and WO22+ have been prepared and their structures elucidated by various physico-chemical studies. The ligand acts as neutral bidentate with VO2+ and neutral monodentate with MoO22+ and WO22+. Infrared spectra suggests cis-dioxo structure for VO2+ and WO22+ but trans dioxo group is present in MoO22+ complexes.